Ethnocultural Problems and Policies in The Republic of Tatarstan, Russia - Refly Setiawan; Gine Putri Pertiwi; Siti Indarini Nur Faizah; Diki Hermawan (STAATSRECHT: Indonesian Constitutional Law Journal, 2021)
This study discusses about ethnocultural problems and policies in the Republic of Tatarstan, Russia with a complex multiethnic population in a condition of balance between the two main ethnic groups, namely Russians and Tatars. In addition, there are historical and ideological views for ethnocultural policy formation in Tatarstan, positive and negative trends in the field of interethnic relations. The author focuses on aspects of ethnocultural policy implementation such as the implementation of the right to receive ethnocultural education and preservation of indigenous languages, support for traditional folk culture, interaction with public ethnic associations, etc. The results of this study illustrate that the existence of a situation in the field of inter-ethnic relations can indicate the end of the ethnocentric policy model in areas that are in favor of the Tatar community in the current conditions of multiculturalism.